ANALYSIS OF RETAILER’S BEHAVIOURAL INTENTION TO USE MOBILE PAYMENT: USING THE UTAUT (UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY) MODEL (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
In this evolving modern world, technology  is involved in all fields of human life. Mobile  payment has become essential not only for  consumer convenience but also for retailers’  business growth. Several studies have been  undertaken to highlight the aspects that  contribute to the establishment of “Behavioural  Intention” among consumers for adopting  mobile payments. Still, no studies are available  in the context of India, as per the review of  literature, which demonstrate the factors  responsible for “Behavioural Intention” of  retailers to adopt and use mobile payment in  their day-to-day business. This study makes use  of a “Five-point Likert Scale” to collect data  from Indian retailers and establish a relationship  between the selected variables for the study  to fill the existing research gap present in the  context of Indian retailers. Apart from UTAUT,  “Performance Expectancy,” “Effort Expectancy,”  “Social Influence,” “Facilitating Conditions,”  and “Behavioural Intention,” “Perceived  Security” is considered as one variable as there  is always a security risk involved in using any  digital technology. It is found that only “Effort  Expectancy” and “Perceived Security” have a  significant relationship with the Behavioural  Intention of a retailer to use mobile payment.  At the same time, “Performance Expectancy,”
Keywords: “Performance Expectancy (P.E)”; “Effort Expectancy (E.E.)”; “Social Influence (S.I.)”,; “Facilitating Conditions (F.C.); “Behavioural Intention (B.I; “Perceived Security (P.S)”